Microbial diversity and probiotic potential of fermented traditional rice varieties: Characterization and functional evaluation - Subaratinam, R; Vidya, R; Suganthi, V (Journal of Food Technology Research, 2025)
This study focuses on the characterization of probiotic diversity derived from two fermented traditional rice varieties, Kattuyanam and Mappillai Samba. The rice samples were processed, lyophilized, and subjected to microbiological analysis. Molecular identification was performed using metagenomics analysis. Probiotic efficacy was evaluated through acid and bile salt tolerance tests, antibiotic susceptibility assays (agar well diffusion), glucose fermentation, and adhesion assays on stainless steel plates. Metagenomic analysis confirmed the dominance of the Firmicutes phylum in both samples, with Lactobacillaceae as the most prevalent family. Antibiotic susceptibility tests revealed varying resistance patterns, with notable resistance to penicillin, streptomycin, and ampicillin, while susceptibility to tetracycline, rifampin, and erythromycin varied between samples. The combination of rice varieties displayed increased susceptibility compared to individual strains. In vitro probiotic efficacy tests demonstrated acid and bile salt tolerance, with the Kattuyanam and Mappillai Samba 1:1 (KRMR) showing the highest survival rates under acidic (80.287±0.328%) and bile salt (78.419±0.285%) conditions. Glucose fermentation tests indicated homofermentative behavior in all isolates, producing lactic acid without gas accumulation. Additionally, adhesion assays revealed that KRMR had the highest adherence to stainless steel (39.333±1.52%), indicating its potential for gut colonization. These findings highlight the probiotic potential of traditional rice-fermented microbes for applications in gastrointestinal health and functional foods.